P–556 NAT10-mediated N4-acetylcytidine in RNA regulates mouse oocyte maturation in vitro. (6th August 2021) - Xiang, Y; Zhou, C; Guo, Q; Liang, X
Abstract: Study question: Does NAT10-mediated N4-acetylcytidine (ac4C) in RNA, a newly identified mRNA epigenetic modification, participate in modulating in vitro maturation(IVM) of oocytes? Summary answer: NAT10-mediated ac4C modification is an important regulatory factor during oocyte maturation in vitro, by regulating genes associated with translation, mitochondrial functions and protein destabilization. What is known already: Unlike somatic cells, transcription and translation are uncoupled during oocyte maturation and gene expression is mainly regulated by post-transcriptional modulation, including mRNA degradation, translation and posttranslational modification, which are complex and have not been fully investigated. RNA ac4C is a newly identified mRNA modification and a key determinant of post-transcriptional regulation, which has been shown to promote mRNA stability and translation, and NAT10 is the only known RNA acetyltransferase. Therefore, NAT10-mediated ac4C represents a possible epigenetic regulator in oocyte maturation. Study design, size, duration: Oocytes at different stages from mice were collected to detect the changing levels of ac4C and NAT10 during maturation. NAT10 in GV-stage oocytes was knocked down before IVM, to confirm the regulatory role of NAT10-mediated ac4C in meiotic process, followed by further exploration of cellular mechanisms. Each experiment was repeated at least three times, and data were analyzed by chi-square test, one-way ANOVA or unpaired-sample t-test. Participants/materials, setting, methods: The expression of ac4C and NAT10 was detected by immunohistochemistry. NAT10 was knocked down in GV-stage oocytes by RNA interference through electroporation. The efficacy of knockdown was confirmed by qPCR and immunohistochemistry targeting ac4C and NAT10, and the percentages of oocytes maturated in vitro were compared among groups. High-throughput sequencing and RNA immunoprecipitation were performed to reveal the modulated genes. Proteins specifically binding to ac4C sites were identified by RNA pulldown and mass spectrometry. Main results and the role of chance: We first retrieved publicly available data from GEO and found that transcripts with potential ac4C sites were enriched in genes downregulated during IVM (P < 0.001). The biased distribution of ac4C implicated a possible regulatory role. Then immunohistochemistry revealed significantly decreasing trends of ac4C and NAT10 expression from immature to mature oocytes. With NAT10 knockdown, ac4C modification was reduced and meiotic progression was significantly retarded. Specifically, the rate of first body extrusion was significantly decreased with NAT10 knockdown (34.6%) compared to control oocytes without transfection (74.6%) and oocytes transfected with control siRNA (72.6%) (p < 0.001), while rates of germinal vesicle breakdown were not affected (P = 0.6531). High-throughput sequencing and RNA immunoprecipitation revealed that the modulated genes were enriched in biological processes known to be associated with oocyte maturation, including translation, mitochondrial translational elongation and termination, and protein destabilization. Also, we identified a series of proteins specifically binding to ac4C probes by RNA pulldown and mass spectrometry, through which ac4C modification may exert its function in post-transcriptional modulation. Limitations, reasons for caution: This study was performed in vitro. The role of NAT10-mediated ac4C in vivo remains to be elucidated. Also, limited by current techniques, ac4C modification in oocytes cannot be detected. Our exploration of regulated genes and ac4C binding proteins were performed in somatic cell lines. Wider implications of the findings: Post-transcriptional modulation is crucial in oocyte maturation. Our study using in-vitro systems for mouse oocyte identified NAT10-mediated ac4C as an important regulator in IVM. It provided a new insight into the epigenetic mechanisms of IVM, which may lead to improvement of clinical IVM systems. Trial registration number: Not applicable